The eucharist as eschatological proclamation, according to St. Paul - Suggit, J. N. (Neotestamentica, 1987)
The meaning of the apocalyptic language used by Paul is shown to be connected to the death and resurrection of Jesus Christ. An examination of Paul's references to the eucharist shows that the eucharist, in referring both to the past event and to the future eschaton, brings past and future together in the present. This meaning of eucharist is shown to be in keeping with Paul's understanding of baptism.